Strategi pengembangan kerajinan anyaman Purun untuk meningkatkan daya saing - Ernawati Ernawati; Ratih Hurriyati; Puspo Dewi Dirgantari (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This research aims to recognize the ability and formulate a strategy of developing woven handicrafts Purun as the flagship product of Banjarbaru City. The approach is based on Porter's intensive strategy. The population in this study was all craftsmen-woven Purun while the sample was two groups of 45 craftsmen woven Purun in Kampung Purun Banjarbaru City. Data collection techniques with interviews, observations, and documents. Analytical techniques with descriptive analysis and SWOT analysis. The results showed that woven handicrafts Purun in Kampung Purun Banjarbaru city have considerable potential to be developed because it is a superior product. Increasing aspects of production, labor, marketing, capital, business management, and organization is an important aspect in the management of business development woven crafts Purun. While the political and regulatory, social and cultural aspects and technology is an aspect that can be an opportunity for the development of woven handicraft business Purun. Development strategy so that woven craft Purun becomes a superior product and can compete in the market is with incentive strategies, namely market penetration strategies, business strengthening strategies and product development strategies.